2016
DOI: 10.1158/1535-7163.mct-15-0765
|View full text |Cite
|
Sign up to set email alerts
|

NQO1-Mediated Tumor-Selective Lethality and Radiosensitization for Head and Neck Cancer

Abstract: Ionizing radiation (IR) is a key therapeutic regimen for many head and neck cancers (HNCs). However, the 5-year overall survival rate for locally-advanced HNCs is ∼50% and better therapeutic efficacy is needed. NAD(P)H:quinone oxidoreductase 1 (NQO1) is over-expressed in many cancers, and β-lapachone (β-lap), an unique NQO1 bioactivatable drug, exploits this enzyme to release massive reactive oxygen species (ROS) levels that synergizes with IR to kill by programmed necrosis. β-Lap represents a novel therapeuti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 29 publications
4
71
0
Order By: Relevance
“…It has been demonstrated that targeting glutamine metabolism, using BPTES sensitizes PC cells to β-lap by enhancing reactive oxygen species as well as PARP activation, leading to enhanced tumor cell specific cytotoxicity [308]. β-lapachone has been shown to be a potential radiosensitizer in a variety of cancers [309,310]. …”
Section: Drugs Targeting Metabolism and Metabolic Enzymes As Radimentioning
confidence: 99%
“…It has been demonstrated that targeting glutamine metabolism, using BPTES sensitizes PC cells to β-lap by enhancing reactive oxygen species as well as PARP activation, leading to enhanced tumor cell specific cytotoxicity [308]. β-lapachone has been shown to be a potential radiosensitizer in a variety of cancers [309,310]. …”
Section: Drugs Targeting Metabolism and Metabolic Enzymes As Radimentioning
confidence: 99%
“…NADPH is also oxidized to NADP + by ribonucleotide reductase to maintain dNTP pools for DNA repair and cell survival following ionizing radiation (18). A synergistic effect is reported when combining sublethal doses of blapachone with radiation therapy in NQO1 + human prostate and head and neck cancers (7,8,34), as well as in non-small cell lung cancers (Boothman, pers. comm.).…”
Section: Introductionmentioning
confidence: 99%
“…Increased consumption of NAD + and ATP, enhanced DNA double-strand breaks, and prolongation of c-H2AX were attributed, in the combined therapy, to result in head and neck squamous cell carcinoma (HNSCC) tumor regression. The competition for NADPH as a substrate for futile redox cycling, reduction of antioxidant defense systems (thioredoxin and glutaredoxin), PARP activity, and as a cofactor for dNTP synthesis upon radiation and chemotherapeutic insult in high NQO1/CAT tumor cells results in selective cytotoxicity (34).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, while the work herein has focused on NSCLC, this drug combination is very likely to be effective in the many other cancer types with overexpression of NQO1, 27, 28 including pancreatic, 53 breast, 54 and head-and-neck cancers. 55 More generally, the potential of different ROS forms to synergize is intriguing and could be a general manner to exploit mechanism-based synergy to induce selective cancer cell death.…”
Section: Resultsmentioning
confidence: 99%